The Nagorno-Karabakh war of 2020 and the change of the regional status quo - Hayrapetyan, Lilit (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The article aims to determine how the change in the status quo in the aftermath of the Karabakh war in 2020 influenced Russia’s position in the region. It strives to answer the question of how this change impacted the geopolitical power balance for Russia. The author used the historical events’ analysis method as well as examined both official information and the opinions of independent experts before attempting to make the most important provisions by comparing, contrasting and analysing these frequently diametrically opposed forecasts and opinions. The author argues that, contrary to some speculations, the situation might have changed not in favour of Russia in the longer run. The Karabakh war of 2020 highlighted the competition between regional powers, including Turkey, in the region and beyond. As a result of the war of 2020, Russia was able to station its peacekeepers in Nagorno-Karabakh but also had to count with Turkey’s substantial influence over the region, which has a tendency to expand to Central Asia and Northern Caucasus. To withstand the regional competition Moscow has charted a policy to foster economic cooperation projects between warring states, to enhance internal cohesion in this post-USSR territory under its guidance. This will allow Russia to transform the South Caucasus into a more or less stable region that will be its buffer belt, with guaranteed non-hostile regimes.

Celem artykułu jest określenie, w jaki sposób zmiana status quo w następstwie wojny karabaskiej 2020 roku wpłynęła na pozycję Rosji w regionie. Autorka stara się odpowiedzieć na pytanie, jak ta zmiana wpłynęła na geopolityczny układ sił Rosji. Autorka posłużyła się metodą analizy wydarzeń historycznych, zbadała zarówno oficjalne informacje, jak i opinie niezależnych ekspertów przed podję ciem najważniejszych zapisów, porównując, przeciwstawiając i analizując te często diametralnie przeciwstawne prognozy i opinie. Autorka przekonuje, że wbrew niektórym spekulacjom sytuacja mogła się zmienić na niekorzyść Rosji w dłuższej perspektywie. Wojna karabaska w 2020 roku uwydatniła rywalizację między mocarstwami regionalnymi, w tym Turcją, w regionie i poza nim. W wyniku wojny z 2020 roku Rosja rozmieściła siły pokojowe w Górskim Karabachu, ale musiała też liczyć się z istotnymi wpływami Turcji w regionie, który ma tendencję do ekspansji na Azję Centralną i Północny Kaukaz. Aby przeciwstawić się regionalnej konkurencji, Moskwa opracowała politykę wspierania projektów współpracy gospodarczej między walczącymi państwami, aby wzmocnić wewnętrzną spójność na tym obszarze poradzieckim. Pozwoli to Rosji na przekształcenie Kaukazu Południowego w mniej lub bardziej stabilny region, który będzie jej pasem buforowym z gwarantowanymi niewrogimi reżimami.
Wojna w Górskim Karabachu z 2020 roku i zmiana regionalnego status quo
Keywords: The Nagorno-Karabakh war of 2020; Russia; Turkey; geopolitics; power balance; wojna karabaska 2020 r.; Rosja; Turcja; geopolityka; równowaga sił